Poverty Dynamics in Rural India - Aziz, Jahangir (IMF Working Papers; Working Paper, 2002)
India's progress in reducing poverty at the national level masks substantial disparity in the incidence of poverty at the state level. This paper provides a description of the trends in interstate differences in rural poverty for the period 1978-97. Key findings are that poverty generally declined in most states over the last twenty years. However, poverty increased during the early years of the 1990s reform period before decline again in the later years. Relative differences in poverty narrowed during the 1980s but widened somewhat during the next decade. The better success rate of some states in reducing poverty in the 1990s was, in part, due to higher growth and lower inflation.